2019
DOI: 10.3390/s19030531
|View full text |Cite
|
Sign up to set email alerts
|

Spaceborne Satellite for Snow Cover and Hydrological Characteristic of the Gilgit River Basin, Hindukush–Karakoram Mountains, Pakistan

Abstract: The Indus River, which flows through China, India, and Pakistan, is mainly fed by melting snow and glaciers that are spread across the Hindukush–Karakoram–Himalaya Mountains. The downstream population of the Indus Plain heavily relies on this water resource for drinking, irrigation, and hydropower generation. Therefore, its river runoff variability must be properly monitored. Gilgit Basin, the northwestern part of the Upper Indus Basin, is selected for studying cryosphere dynamics and its implications on river… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Such an increase in biomass was highly taxa-specific, favoring some species upon others, and thereby modifying community composition. This taxa-specific pattern of plant community responses to warming has been stressed in other studies performed in challenging environmental conditions such as the Arctic [11,35,61–63]. Flower production response to warming was positive in 41% of plants but had no effects on the other taxa.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Such an increase in biomass was highly taxa-specific, favoring some species upon others, and thereby modifying community composition. This taxa-specific pattern of plant community responses to warming has been stressed in other studies performed in challenging environmental conditions such as the Arctic [11,35,61–63]. Flower production response to warming was positive in 41% of plants but had no effects on the other taxa.…”
Section: Discussionsupporting
confidence: 54%
“…The maximum temperature recorded in May goes up to 25°C in the warm year [32] while in winter it drops down below 0°C from October (3590m) [15,33,34]. Annual precipitation ranges from 200 to 900 mm per year [31,35]. Being alpine KNP harbors the following vegetation altitudinal zones: 1) The sub nival zone (> 4500 m) is made of snow and bare desert, covering about 30% of the park’s area.…”
Section: Methodsmentioning
confidence: 99%
“…This finding could be explained by enhanced melting from the observed warming during winter [53,54]. The Khunjerab climate station in Hunza, which is located at 4710 m a.s.l., also shows an increasing trend in both annual and seasonal temperatures [21,55]. On the other hand, earlier studies have shown an increasing trend in the SCA [18,24,33].…”
Section: Discussionmentioning
confidence: 63%
“…The snow cover area was estimated using original and improved MODIS snow products. The original products were also used with the <20% clouds threshold (as commonly used by previous studies [18,21]) for comparison with the improved product. In the products with 20% cloud thresholds, the original Aqua and Terra images with a percentage cloud cover more than 20% were discarded for the comparative assessment among five different products.…”
Section: Snow Cover Area Calculationmentioning
confidence: 99%
“…However, a major area in the UIB is covered with snow and glaciers wherein melting water is used for irrigation, domestic use, and hydropower generation [7]. According to the study of Hussain et al [71], the snow cover showed a decreasing trend in the Gilgit river basin, whereas that of Tahir et al [72] reported a slightly increasing trend in the Hunza river basin.…”
Section: E Ground Water Storage(gws) Anomalies From Gracementioning
confidence: 99%